2020
DOI: 10.1111/jnc.15227
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid induces thrombospondin‐1 production in primary cultured rat cortical astrocytes

Abstract: Lysophosphatidic acid (LPA), a brain membrane‐derived lipid mediator, plays important roles including neural development, function, and behavior. In the present study, the effects of LPA on astrocyte‐derived synaptogenesis factor thrombospondins (TSPs) production were examined by real‐time PCR and western blotting, and the mechanism underlying this event was examined by pharmacological approaches in primary cultured rat cortical astrocytes. Treatment of astrocytes with LPA increased TSP‐1 mRNA, and TSP‐2 mRNA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…TSP-1 is an inducible protein, and its levels have been reported to increase in response to LPA in several model systems. For example, LPA induces TSP1 at the transcriptional level in rat cortical astrocytes through the LPA receptor LPAR1 [62]. LPA has been previously shown to induce TSP1 in PC-3 cells after an 8 h treatment [63].…”
Section: Discussionmentioning
confidence: 99%
“…TSP-1 is an inducible protein, and its levels have been reported to increase in response to LPA in several model systems. For example, LPA induces TSP1 at the transcriptional level in rat cortical astrocytes through the LPA receptor LPAR1 [62]. LPA has been previously shown to induce TSP1 in PC-3 cells after an 8 h treatment [63].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, LPA1 contributes heavily to the LPA network. Emerging reports suggested that LPA induces TSP1 synthesis in cortical astrocytes via LPA1 receptor activation [ 20 ].TSP1 and MIP2 are upregulated in PMN recruitment [ 35 ], MIP2 recruits PMN, and activates the CXCR2 receptor. Likewise, we also revealed that the LPA1 content in the haemorrhage hemisphere reached its peak at 24 h following ICH.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the underlying mechanism behind the LPA1-mediated enhancement of BBB integrity following ICH. Based on emerging evidence, LPA enhances TSP1 release by activating LPA1 in astrocytes [ 20 ]. TSP1 is a regulator of specific chemokines, namely, JE and MIP-2, which can increase PMN recruitment via upregulation of the CXCR2 receptor expression [ 23 , 24 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation